2021
DOI: 10.3390/children8060487
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Cycle: Are Physical Activity and Birth Order Related to the Age of Learning How to Ride a Bicycle?

Abstract: The present article aimed to verify whether the age at which children learn to ride a bicycle is related to their physical activity or birth order. Data were collected from an online structured survey between November 2019 and June 2020. A total of 8614 responses were obtained from 22 countries. The results reveal significant differences in learning age depending on the frequency of physical activity (F(5, 7235) = 35.12, p < 0.001, ηp2 = 0.24). People who engaged in physical activity less than twice a month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Changes in the number of children per family, in the cultural ideals of parenthood and of parental levels of supervision and engagement in play should also be considered ( 55 ). For instance, it has been shown that younger siblings usually learn to cycle earlier than older siblings and only children ( 56 ). Homes, families and schools are powerful environments for empowering cycling enculturation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the number of children per family, in the cultural ideals of parenthood and of parental levels of supervision and engagement in play should also be considered ( 55 ). For instance, it has been shown that younger siblings usually learn to cycle earlier than older siblings and only children ( 56 ). Homes, families and schools are powerful environments for empowering cycling enculturation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data collection was carried out within the scope of the Learning to Cycle project (L2Cycle), which developed a retrospective online survey to access the cycle LA [26]. This retrospective method has been used before to collect the LA of several other milestones, e.g., roll over, sit up, stand alone, walk, first words, smiling or crawling [27,28].…”
Section: Surveymentioning
confidence: 99%
“…It could also be a control parameter for learning how to cycle. Over the years, the process of learning to cycle has undergone changes [ 12 ]. In more recent times, a notable change has been the introduction of the balance bike (BB).…”
Section: Introductionmentioning
confidence: 99%